Analysis of Progress and Challenges of EGFR-Targeted Molecular Imaging in Cancer With a Focus on Affibody Molecules - Weizhi Chen MD; Baozhong Shen MD, PhD; Xilin Sun PhD (Molecular Imaging)
Epidermal growth factor receptor (EGFR)-targeted cancer therapy requires an accurate estimation of EGFR expression in tumors to identify responsive patients, monitor therapeutic effect, and estimate prognosis. The EGFR molecular imaging is an optimal method for evaluating EGFR expression in vivo accurately and noninvasively. In this review, we discuss the recent advances in EGFR-targeted molecular imaging in cancer, with a special focus on the development of imaging agents, including epidermal growth factor (EGF) ligand, monoclonal antibodies, antibody fragments, Affibody, and small molecules. Each substrate or probe, whether it is an endogenous ligand, antibody, peptide, or small molecule labeled with fluorochrome or radionuclide, has unique advantages and limitations. Antibody-based probes have high affinity but a long metabolic cycle and therefore offer poor imaging quality. Affibody molecules promise to surpass antibody-based probes due to their small size, stable chemical properties, and high affinity to the target. Small-molecule probes are safe, have favorable pharmacokinetics, and show high affinity and specificity, in addition to having an ideal size, but are inadequate for delayed imaging after injection due to their fast clearance.